Validación de un método analítico por espectrofotometría UV/Visible para la cuantificación de alcaloides totales - Zavaleta Juarez, Milagritos Elizabeth (2023)
The objective of this thesis report was to validate an analytical method by UV/Visible spectrophotometry for the quantification of total alkaloids using Dragendorff's reagent in a galenic product made from hydroalcoholic extracts containing alkaloids. The developed and validated method was selective in differentiating the analyte from the other excipients. Next, a calibration curve was made in the defined concentration range (0.01- 0.09 mg/mL); in the linearity test, a correlation and determination coefficient of 0.9998 and 0.9997 respectively was found, indicating a good linear correlation between the concentration of alkaloids and the absorbance, in addition the statistical test and the coefficient of variation of the response factor showed conformity. In the same way, the accuracy was evaluated through the recovery, being satisfactory, with a recovery percentage of 100.06% and a coefficient of variation of 0.99%; In addition, in the t student, a t exp lower than t tab (0.197 < 2.306) was obtained, with no significant difference between the average recovery and 100%. On the other hand, the precision was evaluated through the analysis of repeatability and intermediate precision and showed a relative standard deviation of 0.99% and 0.88%, being below 2%, which indicates a high precision of the method. Finally, robustness was evaluated by varying the pH and centrifugation speed, producing precise and accurate results under different operating conditions. In conclusion, it was established that the study provided and recorded the necessary evidence to show that the spectrophotometric method is fast, simple and easy, complying with the criteria established by international standards, providing confidence in the determination of precipitable alkaloids, being a useful tool in quality assessment